Efektifitas PBL terhadap Kemampuan Pemecahan Masalah pada Kelas V Tema 5 Ekosistem Subtema 2 Hubungan Antar Makhluk Hidup dalam Ekosistem di SD Supriyadi - Devi Ariyanti Lestari; Husni Wakhyudin; Farida Nursyahidah; Aini Istikomah (Departement of Mathematics Education, 2023)
Educators play an important role in the teaching and learning process in schools. Students will easily understand learning material if it is delivered in an effective way. Currently, the world of education requires student-centered learning by using a learning model, one of which is problem-based learning, therefore researchers are interested in raising research with the title